Processing of retransmitted GPS signals in the problem of measuring the total electron content in the ionosphere - Y. A. Kapliarchuk; S. V. Kozlov; I. E. Savinykh; A. S. Shapkin (Informatika)
Objectives. For a method for estimating the total electron content in the ionosphere based on the retransmission of the L1 GPS navigation signal by a repeater nanosatellite (SR) to the frequencies of 150/400 MHz allocated for geophysical research and their reception at a ground-based receiving point (RP), it is necessary to develop the algorithms for coherent accumulation of received relayed signals and measurement of the difference between their delays at observation intervals up to a few seconds.Methods. The proposed algorithms provide phase demodulation of the received signals at each of the relay frequencies in accordance with the dynamics of the mutual spatial movement of the navigation satellite (NS), SR and RP; multiplying the result by the estimate of the navigation message combined time delay, generated by the receiver of the direct navigation signal on the NS-RP route, intra-period processing over the entire duration of the observation in a filter matched with the signal of the navigation satellite, and inter-period coherent accumulation of the results of intra-period processing at a single-valued range interval. Coherent accumulation, taking into account a random uncontrolled shift in the frequency of the retransmitted signal, is implemented by discrete Fourier transform of the vectors formed for each resolution element in the delay time from inter-period readings of the results of intra-period processing, taking into account the range migration during the mutual movement of the NS, SR and RP.Results. It is shown that by the output signal of the coherent accumulator makes it is possible to detect retransmitted signals at each of the retransmission frequencies, to measure accurately the difference in delay times, and estimate the total electron content on the SR-RP path. The results of modeling are presented, confirming the efficiency of the proposed algorithms in estimating the total electron content on the SR-RP route.Conclusion. An algorithm for coherent accumulation of received retransmitted signals and measurement of the difference between their delays is developed, and its simulation is performed. The algorithm can be used for estimating TEC based on the retransmission of signals from GPS.